Impact of urease and nitrification inhibitor on NH4+ and NO3− dynamic in soil after urea spring application under field conditions evaluated by soil extraction and soil solution sampling. Issue 3 (18th March 2019) - Kirschke, Tobias; Spott, Oliver; Vetterlein, Doris
Abstract: The application of mineral nitrogen (N) fertilizers is one of the most important management tools to ensure and increase yield in agricultural systems. However, N fertilization can lead to various ecological problems such as nitrate ( NO 3 - ) leaching or ammonia and nitrous oxide emissions. The application of N stabilizers ( i.e ., inhibitors) combined with urea fertilization offers an effective option to reduce or even prevent N losses due to their regulatory effect on ammonium ( NH 4 + ) and NO 3 - release into the soil. The present field experiment therefore aimed at soil N speciation dynamics after urea spring fertilization (225 kg N ha −1 ) in the presence of a urease inhibitor (UI), a nitrification inhibitor (NI), both inhibitors (UI+NI) or when no inhibitor was applied at all. The study focused on the distribution of N species among soil matrix and soil solution. Plant cultivation was completely omitted in order to avoid masking soil N turnover and speciation by plant N uptake and growth dynamics. Application of UI clearly delayed urea hydrolysis in the top soil, but a complete hydrolysis of urea took place within only 10 days after fertilization (DAF). Nitrification was significantly reduced by NI application, leading to higher NH 4 + - N and lower NO 3 - - N concentrations in treatments with NI. Due to sorption of NH 4 + to the soil matrix a significantly larger fraction of NH 4 + was always detected in the soil extracts compared to soil solution. However, while in soil extracts the impact of NI application was less apparent and delayed, in soil solution a quick response to NI application was observed as revealed by significantly increased soil solution concentrations of NH 4 + . Because of the "asymmetric" soil phase distribution soil solution NH 4 + was predominant over NO 3 - only initially after fertilization even in inhibitor treatments (≈ 8 to 10 DAF). Nevertheless, inhibitor application tended towards closer ratios of NH 4 + to NO 3 - concentration in soil solution and hence, might additionally affect concentration dependent processes like plant N uptake and root development. Despite cold spring conditions urea application along with UI and/or NI did not indicate a limited supply of plant available NH 4 + and NO 3 - .